2009
DOI: 10.1007/s00226-009-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Application areas of synchrotron radiation tomographic microscopy for wood research

Abstract: Possible applications for synchrotron radiation tomographic microscopy in the field of wood research were tested and evaluated at the TOMCAT beamline (TOmographic Microscopy and Coherent rAdiology experimenTs) at the Swiss Light Source (SLS) at the Paul Scherrer Institute (Villigen, Switzerland). For this study, small cylindrical samples ([ 1 and 3 mm) were examined with different experimental setups resulting in a nominal voxel size of approximately 1.48 9 1.48 9 1.48 and 3.7 9 3.7 9 3.7 lm 3 , respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…To date, the majority of wood XCT studies have used conventional reconstruction methods, such as the filtered backprojection algorithm, and relied on absorption contrast for material identification and differentiation (Hass et al 2010;Mannes et al 2010;Modzel 2009;Modzel et al 2011;Paris et al 2014;Trtik et al 2007). In microscale analyses, absorption contrast is typically adequate for studying anatomical cellular features in solid wood, as only two materials, air and wood cell wall, are present.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of wood XCT studies have used conventional reconstruction methods, such as the filtered backprojection algorithm, and relied on absorption contrast for material identification and differentiation (Hass et al 2010;Mannes et al 2010;Modzel 2009;Modzel et al 2011;Paris et al 2014;Trtik et al 2007). In microscale analyses, absorption contrast is typically adequate for studying anatomical cellular features in solid wood, as only two materials, air and wood cell wall, are present.…”
Section: Introductionmentioning
confidence: 99%
“…For softwoods, several studies identified strong gradients between earlywood (EW) and latewood (LW) with respect to cell geometry, swelling, shrinkage, elastomechanical properties, and density (Harris and Meylan 1965;Fengel and Stoll 1973;Eder et al 2009;Taguchi et al 2011). High-resolution techniques (0.5-1 μm voxel size), such as micro-computer tomography, offer insight in the 3D response toward moisture changes (Trtik et al 2007;Mannes et al 2010;Derome et al 2011) but are restricted to a few cell layers being simultaneously imaged. Derome et al (2011) found pronounced anisotropic swelling and shrinkage for the low-density EW, with lowest strain in the radial direction, whereas the high-density LW showed an almost isotropic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The associated data processing allows acquisition of spatial information even of subcellular structures with a resolution of 0.35 μ m Stampanoni et al 2006a,b ) and observations of different anatomical elements. Both methods provided useful data from in situ mechanical experiments with wood (Trtik et al 2007 ;Walther and Thoemen 2009 ;Hass et al 2010 ;Mannes et al 2010 ), either by means of manual or automatic testing devices (Badel et al 2008 ;Forsberg et al 2008 ). Suitable testing devices seem to be a bottleneck in this type of experiments.…”
Section: Introductionmentioning
confidence: 99%